The Digital Learning Edge: Quality MOOCs and IT Employee Productivity - Nagar, Aarti; Dixit, Sweta (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study investigates the influence of massive open online courses (MOOCs) on employee performance in the information technology (IT) sector, focusing on the quality of MOOCs as defined by trainer-centred and learner-centred approaches. Utilising a structured questionnaire distributed to 400 IT professionals and analysed through structural equation modelling (SEM), the study finds that both dimensions of MOOC quality positively impact employee performance behavioural and result-based. The number of MOOCs completed demonstrates a stronger positive association with employee performance, particularly among those who have completed more than three courses. The findings provide useful guidance for designing corporate learning strategies in IT sectors and add to the growing research on how digital learning improves workplace performance for employees.